Association between distance to nearest supermarket and provision of fruits and vegetables in English nurseries. (July 2017) - Burgoine, Thomas; Gallis, John A.; L. Penney, Tarra; Monsivais, Pablo; Benjamin Neelon, Sara E.
Abstract: With 796, 500 places available for children in England, pre-school nurseries could serve as an important setting for population-wide dietary intervention. It is critical to understand the determinants of healthy food provision in this setting, which may include access to food stores. This study examined the association between objective, GIS-derived supermarket proximity and fruit and vegetable serving frequency, using data from 623 English nurseries. Overall, 116 (18%) nurseries served fruits and vegetables infrequently (<2–3 times/week), but provision differed by supermarket proximity. In adjusted multivariable regression models, nurseries farthest from their nearest supermarket (Q5, 1.7–19.8 km) had 2.38 (95% CI 1.01–5.63) greater odds of infrequent provision. Our results suggest that supermarket access may be important for nurseries in meeting fruit and vegetable provision guidelines. We advance a growing body of international literature, for the first time linking the food practices of institutions to their neighbourhood food retail context. Highlights: We examined the relationship between nursery supermarket access and the provision of fruits and vegetables to children. We used data from a representative sample of 623 English nurseries, alongside objectively measured supermarket proximity. 18% of nurseries served fruits and vegetables infrequently, but this differed systematically by supermarket proximity. Nurseries farthest from their nearest supermarket were significantly less likely to serve fruits and vegetables frequently. Supermarket access may be important for nurseries in meeting guidelines for the provision of fruits and vegetables.